Drug Policies and Development : Conflict and Coexistence - Buxton, Julia; Chinery-Hesse, Mary; Tinasti, Khalid; Buxton, Julia; Chinery-Hesse, Mary; Tinasti, Khalid (Brill, 2020)
The 12th volume of International Development Policy explores the relationship between international drug policy and development goals, both current and within a historical per-spective. Contributions address the drugs and development nexus from a range of critical viewpoints, highlighting gaps and contradictions, as well as exploring strategies and oppor-tunities for enhanced linkages between drug control and development programming. Crim-inalisation and coercive law enforcement-based responses in international and national level drug control are shown to undermine peace, security and development objectives. Readership: Academic scholars and researchers, policymakers and development practitioners interested in international development policy, drug policies and their effects on development, global economic and political trends, and local development issues.
English
Keywords: International relations; International relations